Independent determination of symmetry and polarity in the Drosophila eye. - Choi, K.W.; Mozer, B.; Benzer, S. (Proceedings of the National Academy of Sciences of the United States of America, 1996)
In each facet of the Drosophila compound eye, a cluster of photoreceptor cells assumes an asymmetric trapezoidal pattern. These clusters have opposite orientations above and below an equator, showing global dorsoventral mirror symmetry. However, in the mutant spiny legs, the polarization of each cluster appears to be random, so that no equator is evident. The apparent lack of an equator suggests that spiny legs+ may be involved in the establishment of global dorsoventral identity that might be essential for proper polarization of the photoreceptor clusters. Alternatively, a global dorsoventral pattern could be present, but spiny legs+ may be required for local polarization of individual clusters. Using an enhancer trap strain in which white+ gene expression is restricted to the dorsal field, we show that white+ expression in spiny legs correctly respects dorsoventral position even in facets with inappropriate polarizations; the dorsoventral boundary is indeed present, whereas the mechanism for polarization is perturbed. It is suggested that the boundary is established before the action of spiny legs+ by an independent mechanism.